2015
DOI: 10.1063/1.4936167
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analysis of doped/undoped ZnO nanomaterials using laser assisted atom probe tomography: Influence of the analysis parameters

Abstract: International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
29
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 37 publications
3
29
0
Order By: Relevance
“…Figure 8 shows the evolution of Ti and D composition as a function of the (Ti 2+ +TiD 2 2+ )/TiD + ratio measured in both instruments. Generally, the D composition tends to increase with increasing surface electric field, similarly to other compounds composed of metallic and non-metallic elements, where the compositions of the non-metallic elements increase with the increasing surface field [19,20]. At low field (high LPE), the measured D compositions in both the LEAP 5000XR and the LEAP 5000XS atom probes are lower than the nominal value defined by the stoichiometry of TiD 1.91-1.99 deuteride, and increase as the field increases in the same trend.…”
Section: Laser Pulsingmentioning
confidence: 96%
See 2 more Smart Citations
“…Figure 8 shows the evolution of Ti and D composition as a function of the (Ti 2+ +TiD 2 2+ )/TiD + ratio measured in both instruments. Generally, the D composition tends to increase with increasing surface electric field, similarly to other compounds composed of metallic and non-metallic elements, where the compositions of the non-metallic elements increase with the increasing surface field [19,20]. At low field (high LPE), the measured D compositions in both the LEAP 5000XR and the LEAP 5000XS atom probes are lower than the nominal value defined by the stoichiometry of TiD 1.91-1.99 deuteride, and increase as the field increases in the same trend.…”
Section: Laser Pulsingmentioning
confidence: 96%
“…However, the LPE cannot be used as a reliable parameter to directly compare the measurements on different specimens and on different instruments as it is related to the standing voltage, specimen geometry and the conversion of the laser illumination into a thermal pulse [43,44]. Instead, the surface field, reflected by the charge-state ratio of metallic elements, has often been used for direct comparison between experiments in the cases of compounds such as GaN, ZnO, etc [19,20]. However, in our experiments, only one charge state of Ti, i.e.…”
Section: Laser Pulsingmentioning
confidence: 99%
See 1 more Smart Citation
“…This behavior can be partially explained through preferential evaporation of the metallic element at high field, while the mechanism responsible of the loss of N or O at low field is still under debate. Neutral evaporation or production of neutral N and O upon dissociation of more complex molecules have been proposed [1][2][3][4][5][6]8]. The field dependence of the measured composition also implies that the measurement is not uniform on the tip surface, as the field itself varies due to the specimen geometry and crystallography ( Fig.…”
mentioning
confidence: 99%
“…This is possible under the hypothesis that all elemental species are field evaporated and detected with the same rate. However, recent studies have shown that for certain materials this hypothesis does not hold [1][2][3][4][5][6]. It becomes then necessary to explore the field evaporation behavior of compound semiconductors in order to (i) assess whether there is a bias in the compositional measurement (ii) understand what are the physical mechanisms inducing a bias and (iii) correct the bias, if possible.…”
mentioning
confidence: 99%